Perancangan Mesin Perontok Padi yang Ekonomis untuk Membantu Petani di Desa Sukarame Tasikmalaya - Ahmad Zamakhsyari Sidiq; Iwan Kurniawan; Jejen (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Sukarame Village is one of the villages in Sukarame District, Tasikmalaya Regency which has a fairly large rice field area. The problem faced by farmers in Sukarame village is that the thresher used so far is salome, which in its use requires quite a lot of time and energy, thus making farmers tired. There are already effective rice threshing machines in the market, but they are quite expensive, so not all farmers can have them. Thus, a threshing device is made, and does not require energy to use. The results of the testing of this tool showed that of the 30 farmers interviewed, all of them said they were comfortable, and the yield of threshing rice per day increased.